0017 Genetic Polymorphisms Of Sleep Resilency, Sleep Intensity, Morning Preference, And Caffeine Sensitivity Are Not Associated With Neurobehavioral Performance Under Repeated Cycles Of Total Sleep Deprivation. (27th April 2018) - Brager, A; Grant, D; Satterfield, B; Ratcliffe, R; Capaldi, V; Balkin, T; van Dongen, H; Petrovick, M
Abstract: Introduction: Previous studies have identified intra-individual variability in neurobehavioral performance under total sleep deprivation (TSD). It is hypothesized that intra-individual variability is under genetic regulation. Here, we examined intra-individual variation in targeted single-nucleotide polymorphisms (SNPs) associated with: a) resistance to sleep deprivation (ADORA2A [7 variants]; TNF-alpha, ADA1); b) morning preference (PER1, PER2); c) sleep intensity (BDNF); and d) daytime sleepiness (COMT) under one of the longest regimens of TSD conducted in sleep research. Methods: 12 subjects (6 males) underwent three cycles of 48 h of TSD separated by three days of recovery sleep (8 h, TIB). During TSD, caffeine was administered every 12 h at 13:00 and 01:00 (0 mg, 200 mg, and 300 mg) concurrently with the psychomotor vigilance test (PVT) to examine neurobehavioral performance. Results: There was no significant association between the targeted SNPs and neurobehavioral responses to sleep deprivation (p> 0.05, all). One ADORA2A SNP (rs2298383) did show a trend towards association with PVT lapses (p=0.049, non-adjusted) and reaction time (p=0.066, non-adjusted). There was no significant association between the targeted SNPs and caffeine preservation of neurobehavioral performance under sleep deprivation. One CYP1A SNP (rs762551) did show a trend towards association with PVT lapses (p=0.08, Bonferroni-adjusted). Conclusion: We observed that targeted SNPs associated with sleep resiliency and caffeine sensitivity are loosely associated with neurobehavioral impairment under repeated cycles of TSD and possession of a unique SNP may not be enough to overcome the deleterious effects of total sleep deprivation. However, given that the trends observed agree with previous work, repetition with a larger cohort is warranted. Support (If Any): Department of Defense Military Operational Medicine Program